Multiple use of water and water productivity of communal small dams in the Limpopo Basin, Zimbabwe - Senzanje, Aidan; Boelee, Eline; Rusere, S. (2008)
The history of dam construction in Zimbabwe dates back to the 1920s and since then over 7,000 small dams have been constructed countrywide. Small dams are multipurpose structures used for improving rural livelihoods. The multipurpose nature of these dams has largely gone unquantified in terms of importance of the uses to the community and influence of management practises. The current study made use of a questionnaire among small dam users, key informant interviews, secondary data and observation on four communal dams in the Limpopo basin to establish the uses, volume of water abstracted and water productivity for some uses and the interrelationship between various organisations and the community in the management of small dams. Uses on all dams in order of importance were livestock watering, domestic use, irrigation, fishing, brick making, and collection of reeds used for roofing. Livestock consume on average over 70% of water for consumptive uses. Water productivity in terms of yield per volume unit of water used ranged from 0.025 kg m-3 for vegetables to 7,575 kg m-3 for bricks, and monetary values per volume unit of water used were Z$ 389,434 m-3 for brick making and Z$ 1,874 m-3 for irrigation. Traditional leadership and the community are pivotal in the management of the small dams, with some organisations giving technical, financial and input assistance. The management and conservation of small dams needs to be well coordinated between the communities, NGOs and government if the full benefits of these national resources are to be realised in the long term.